Інтер’єр в архітектурі культурного комплексу Трипілля-Кукутень (проблеми вивчення, інтерпретації та реконструкції) - Бурдо, Н.Б. (Археологія і давня історія України, 2020)
У статті йдеться про основні проблеми вивчення, інтерпретації й реконструкції інтер’єру в архітектурі Трипілля-Кукутені. The interior of Trypillian houses is not as available object as the interior of the folk architecture to which it actually belongs. The necessary steps to study the interior of Copper Age houses from archeological sites are: • field research and advanced fixation in field documentation of detected interior details / remains; • interpretation of discovered archaeological data; • reconstruction of identified structural elements — the ultimate goal of the study which can be carried out on the basis of the interpretation of archeological objects using the method of study of buildings used by ethnology. It is necessary to take into account the sacral load of all elements of the dwelling, as well as the factor of transformation of them in the final stage of the settlement’s life into a ritual object. Formally, the following clay interior details can be distinguished: I — various enhancements, including rectangular and round elevations, side elevations, cruciform elevations, and catwalks; II — special clay storage tanks; III — furnaces. The analysis of the interior of Cucuteni—Trypillya dwellings shows the unity of the architectural tradition from the early up to the final stages. The origins of these traditions are related to the interior and ritual sphere of dwellings and settlements discovered in the oldest Neolithic Cultures of Europe. Clay interior details are characteristic of the architecture of the neoneolithic crops of South-Eastern Europe. They are especially often recorded in buildings that were burned in ritual fires. Clay interior designs including in the form of rectangular and circular elevations are recorded in buildings of such cultures as Hamangia III, Boyan, Vedastra, different variants and periods of Vinca Culture. The rituals, similar to Trypillian ones, associated with rituals, known in the cultures of Tisza, Kojaderman- Karanovo-Gumelnitsa, Selkutsa.